2016
DOI: 10.1186/s40795-016-0101-7
|View full text |Cite
|
Sign up to set email alerts
|

Low mid-upper arm circumference identifies children with a high risk of death who should be the priority target for treatment

Abstract: Background: Severe acute malnutrition (SAM) is currently defined by the WHO as either a low mid-upper arm circumference (i.e. MUAC <115 mm), a low weight-for-height z-score (i.e. WHZ <− 3), or bilateral pitting oedema. MUAC and WHZ do not always identify the same children as having SAM. This has generated broad debate, as illustrated by the recent article by Grellety & Golden (BMC Nutr. 2016;2:10). Discussion: Regional variations in the proportion of children selected by each index seem mostly related to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 42 publications
3
85
1
1
Order By: Relevance
“…MUAC, therefore, may not be sufficiently sensitive for this population. This is of concern, particularly considering MUAC is a preferred measure for admission to therapeutic and supplementary feeding programmes . One possible reason for the discrepancy could be that children with CP mobilize more with their arms and thus MUAC is built up more than in other children, although as more than half of children were in the severe GMFCS category and would likely have weak spastic muscles this is unlikely to fully account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…MUAC, therefore, may not be sufficiently sensitive for this population. This is of concern, particularly considering MUAC is a preferred measure for admission to therapeutic and supplementary feeding programmes . One possible reason for the discrepancy could be that children with CP mobilize more with their arms and thus MUAC is built up more than in other children, although as more than half of children were in the severe GMFCS category and would likely have weak spastic muscles this is unlikely to fully account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…MAM is currently defined by two criteria: weight‐for‐height z score (WHZ) between −2 and −3 and/or a mid‐upper arm circumference (MUAC) between 115 and 125 mm (WHO, UNICEF, WFP and UNHCR, ). Whether WHZ‐ or MUAC‐based criteria are more suitable for identifying children in need of treatment is still under debate (Briend et al, ; Grellety & Golden, ; Hossain et al, ; Tadesse, Tadesse, Berhane, & Ekström, ), but children falling under each of the categories have not yet been well characterised, including with regard to their motor and language development. The association of linear and ponderal growth with child development has been reported from several low‐ and middle‐income settings (Adair et al, ; Prado et al, ; Worku et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is clear that more evidence is needed on specific aspects of combined/simplified protocols before national decision‐makers will substantially revise national protocols. For example, the hesitancy to adopt MUAC and oedema‐only diagnosis observed in our study is understandable given the lively and ongoing scientific debate on this topic (Briend et al, ; Grellety & Golden, ). Compared with WHZ, there is broad agreement that MUAC constitutes the superior measure for use in community screenings, as well as in emergency situations, where obtaining WHZ is often infeasible.…”
Section: Discussionmentioning
confidence: 82%
“…Although some analyses have suggested that up to three‐quarters of severely malnourished children are missed by MUAC <115 mm criteria (Grellety & Golden, ), most proposed MUAC‐only protocols use a higher threshold than 115 mm. Interventions have sometimes used the sitting height to standing height ratio (or Cormic index) to correct of weight‐for‐height measurements for the body morphology of some ethnic groups (Roberfroid et al, ; Salama et al, ), but the issue of geographical variations body shape requires further study (Briend et al, ). Evolving understandings of the frequency of multiple anthropomorphic deficits and the overlap and dynamic interactions between wasting and stunting will also influence this debate (Myatt et al, ; Wells et al, ).…”
Section: Discussionmentioning
confidence: 99%